Problems, success factors and benefits of ICCs implementation: a case of Naza Automotive Manufacturing Sdn. Bhd. (NAM) / Noraiffa Md Yusuf ... [et al.] - Md Yusuf, Noraiffa; Muhamad Lutpi, Hatmah; Mohd. Zaki, Nur Azini (2012)
ICC projects deal with problem solving and quality issues. ICCs focus to include innovative projects that will ensure enterprise competitiveness and enhances business growth. In NAM, ICC is formed in the year of 2005 while the program is actively organized in 2006. ICC has been scheduled as an annual event for the purpose of value improvements in an existing process or to implement a new process, product or service in NAM. The purpose of this study is to identify the problems that Naza Automotive Manufacturing Sdn. Bhd (NAM) typically encounter in implementing Innovative and Creative Circles (ICCs); to identify weaknesses, opportunities and threats attributed to the implementation of ICCs in NAM; identify the critical success factors promoting ICCs implementation and to recommend strategic approach to ensure ICC is effectively organize in NAM. The data for this study were collected using a self-administered questionnaire that was distributed to 120 ICCs members from various departments. Of the 120 questionnaires distributed, a total of 59 or 49.20 percent were returned and used for the analysis. The results of the study indicated that lack of support from top management was reported as the biggest threat impeding the implementation of ICC at NAM; Teamwork and communication were reported as the most important success factor of ICCs implementation in NAM. It is followed by comprehensive training, top management support and the level of skills and knowledge among workers as factors contributed towards successful implementation of ICCs in NAM respectively. More importantly, the findings indicated that ICCs implementation has increase productivity, reduce costs and improving the management style. The findings have practical implications to all the departments at NAM.